2021
DOI: 10.1002/aepp.13166
|View full text |Cite
|
Sign up to set email alerts
|

Impact of changes in the frequency of food pantry utilization on client food security and well‐being

Abstract: Food pantries have traditionally focused on meeting emergency food needs. However, for many clients, food assistance is a long‐term need. The frequency with which long‐term clients visit food pantries varies; and in general, visiting frequency has been understudied because the focus has largely been on emergency, rather than long‐term, food assistance impacts. We leveraged a program innovation to identify the impact of visiting frequency on client outcomes. Using fixed‐effect models, we analyzed a panel of 166… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…This includes increasing funding to support various social safety net programs and deliberate efforts to ensure equitable access to the services offered through these programs across race and ethnic groups. Also, as most high-capacity food pantries in the country receive financial support from the US Department of Agriculture (USDA) (Leonard et al , 2021), increasing funding to support private emergency food assistance should be pursued as policy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This includes increasing funding to support various social safety net programs and deliberate efforts to ensure equitable access to the services offered through these programs across race and ethnic groups. Also, as most high-capacity food pantries in the country receive financial support from the US Department of Agriculture (USDA) (Leonard et al , 2021), increasing funding to support private emergency food assistance should be pursued as policy.…”
Section: Resultsmentioning
confidence: 99%
“…A review of related literature shows that our finding is similar to other studies that examine the association between social support and food security/food sufficiency in recent times in the USA. For example, Leonard et al (2021) found evidence that a food pantry decreased household food insecurity during the COVID-19 pandemic in the USA. In addition, Raifman et al (2021) found that receiving UI reduces the household risk of food insecurity by a third and halves the likelihood of needing to eat less because of financial constraints during the COVID-19 pandemic in the USA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study makes a unique contribution to research on food bank services, a sector that has grown in recent decades (Bhattarai et al, 2005;Byrne & Just, 2022;Coleman-Jensen et al, 2015;Coleman-Jensen et al, 2021b). Studies have shown that increased food pantry use is associated with reduced food insecurity (Leonard et al, 2022) and improved weight and diabetes control among clients (Eicher-Miller, 2020). Furthermore, research has documented pantries that have introduced interventions to encourage clients to procure healthier options (An et al, 2019).…”
mentioning
confidence: 88%